STRATEGI MENGHADAPI TANTANGAN DAKWAH AGAMA ISLAM DI ERA MEDIA DIGITAL - Muhammad Raffi; Fatimah Azzahra Mustofa; Masyita Angelia Pamboke; Edi Suresman (EL- Hayah, 2024)
This research addresses the challenges of Islamic religious proselytization in the digital media age. New strategies and approaches are needed with the advent of digital media platforms like Instagram, X, Youtube, and podcasts. One significant hurdle is the presence of an overwhelming amount of information, which includes misleading narratives that can shape incorrect understanding of Islam. Moreover, the prevalence of anonymous accounts and influencers without expertise in Islamic knowledge poses a challenge in establishing trustworthiness. To overcome these challenges and effectively convey religious messages, adaptations in language use, content design, and interactive approaches are necessarry. This research aims to analyze the challenges of preaching in the digital era and provide more effective strategies in accordance with current developments. Challenges of preaching in digital media include the validity of sources, digital divides between social groups, and radical and extremist ideologies. The results of this study indicate that there are challenges to preaching in digital media, including the validity of sources, digital divides between social groups, and radical and extremist ideologies. The preaching strategies that can be applied are improving preacher skills, optimizing social media, and careful planning.